Self-Consciousness Based Religious Education - Öz, Ayhan (Fırat University, 2022)
This study aims to contribute to the solution of the basic problems experienced in the Enlightenment and post-enlightenment process with a religious education approach that focuses on self-consciousness. In the study, firstly, the concept of “self” was examined; then, the main problems experienced by Western human conception that emerged after the Enlightenment, especially false self-construction, individualism, loss of meaning, and separation from the metaphysical field were briefly discussed. In the following parts of the study, the question regarding the function attributed to education in the in the contemporary period was addressed, and in the last part, the ability of religious education to offer solutions to the crises of modern people was discussed. In the study, the importance of human returning to himself with all his abilities and trying to get to know and comprehend himself was emphasized; and it was concluded that the scientific paradigm, which dominates modernity and later, is incomplete in introducing the human to himself with all his aspects. At this point, it was emphasized that a religious education that introduces a person to his own self contains important opportunities and in addition to this, it was pointed out that there is a need for a Muslim typology equipped with self-consciousness, more than ever, due to the peculiar conditions of the period in which it is lived. In short, it is suggested that religious education processes should be made more functional for the modern individual by adding a new dimension to religious education through self-consciousness.

Bu çalışma, modern dönem insanın yaşadığı temel sorunların çözümüne benlik bilincini merkeze alan bir din eğitimi yaklaşımıyla katkı sunmayı amaçlamaktadır. Çalışmada öncelikle “benlik” kavramı üzerinde durulmuş; ardından modern dönem insanının yaşadığı başlıca sorunlar, özellikle de sahte benlik inşası, bireycilik, anlam yitimi, metafizik alandan kopuş gibi temalar üzerinden kısaca ele alınmıştır. Çalışmanın ilerleyen bölümlerinde modern dönemde eğitime yüklenen işlevin ne olduğu konusuna temas edilmiş, son bölümde ise din eğitiminin modern insanın krizlerine çözüm sunma kabiliyeti tartışılmıştır. Çalışmada insanın tüm kabiliyetleriyle kendine dönmesinin, kendini tanımaya ve kavramaya çalışmasının önemi üzerinde durulmuş; modern dönem bilim paradigmasının insanı bütün yönleriyle kendine tanıtmakta eksik kaldığı tespitine yer verilmiştir. Bu noktada insanı öz benliğiyle tanıştıracak bir din eğitiminin önemli imkanlar barındırdığı vurgulanmış; modern dönemin kendine mahsus şatları gereği benlik şuurunu kuşanmış bir Müslüman tipolojisine her zamankinden daha fazla ihtiyaç duyulduğu hususuna dikkat çekilmiştir. Ezcümle, benlik bilinci üzerinden din eğitimine yeni bir boyut eklenmesi; bu sayede din eğitim süreçlerinin modern birey için daha işlevsel kılınması önerilmiştir.
Benlik Bilinci Temelli Din Eğitimi
Keywords: Religious Studies; Din Araştırmaları